Performance Evaluation of Simrs Utilization in Optimizing Patient Services at the PKU Muhammadiyah Clinic in Nort Lombok - Andi Setiawan Tahang; A Rohendi; Yen Efawati (CV. Era Digital Nusantara, 2026)
This study evaluated the utilization performance of the Hospital Management Information System (Sistem Informasi Manajemen Rumah Sakit/SIMRS) in optimizing outpatient and inpatient services at the PKU Muhammadiyah Clinic, North Lombok, Indonesia, and identified key constraints and improvement measures. A qualitative evaluative design was applied using direct observation, semi-structured interviews with ten informants (clinic staff and patients), and document analysis. Data were analyzed using an interactive qualitative analysis approach and credibility was strengthened through source and method triangulation. The findings indicate that SIMRS supports improved access to patient information, reduced administrative workload, and more convenient service procedures. However, optimization remains limited due to uneven user competence and digital literacy, insufficient training, outdated hardware, unstable internet connectivity, and incomplete system menus that require parallel manual processing. These constraints contribute to data inconsistencies, fragmented workflow integration, and challenges in insurance claim processes. Improving SIMRS performance requires integrated socio-technical interventions, including continuous capacity building, clearer user guidance and accountability for data entry, infrastructure upgrades, system refinement aligned with clinical workflows, and sustained organizational commitment.